Effect of deposition methods on microstructure and mechanical properties of Al 7075 alloy-rice husk ash surface composites using friction stir processing - Patil, N.A. (Elsevier Ltd, 2019)
In this study, friction stir processing (FSP) technique was used to fabricate rice husk ash (RHA) reinforced aluminum 7075 alloy (AA7075) surface composites (SCs). In which, deposition method of RHA into AA7075 substrate has been taken as a variable and its effects on microstructure, microhardness and tensile properties of resultant SCs were analyzed. The deposition methods used were- zigzag pattern surface blind holes, linear pattern surface blind holes and grooves pattern method. The microhardness increased in all methods AA7075/RHA SCs than base alloy. In particular, AA7075/RHA SCs by linear pattern surface blind holes method showed higher microhardness than other methods SCs and base alloy. The maximum microhardness of 604 HV obtained for SC processed with linear pattern blind holes method. However, tensile strength of all SCs were found lower than AA7075 alloy. Amongst SCs, zigzag blind holes method processed SCs exhibited higher tensile strength than others. Though SEM imaging confirmed good distribution of RHA particles, certain defects such as agglomeration of particles and tunnels were present within processed zone of SCs. The energy dispersive X-ray analysis (EDX) tests confirmed presence RHA particles in the form of silicon oxides (SiO2), aluminum oxides (Al2O3) etc. as constituents. Thus, AA7075/RHA SCs were fabricated successfully using FSP with increased microhardness properties, further optimization of FSP process parameters needed in order to avoid defects in the resultant materials. Â© 2019 Elsevier Ltd. All rights reserved.